Metastatic Squamous Cell Carcinoma Presenting as Symptom of AIDS - Caroline Brereton BS; Alexander Bravo BS; Whitney Hovenic MD (SAGE Publishing, 2022)
The development of metastatic cutaneous squamous cell carcinoma in an otherwise healthy and young individual should prompt physicians to investigate for an underlying cause of immunosuppression. The following case presents an individual who underwent Mohs surgery of a poorly differentiated squamous cell carcinoma. Four months following Mohs surgery, the patient presented with lymphadenopathy and new skin nodules. Metastatic disease or infection were included in the differential diagnosis. An immunosuppression work-up was completed and the patient was diagnosed with human immunodeficiency virus (HIV). Treatment with antiretroviral therapy was initiated 1 month prior to treatment of the metastatic disease with an immunomodulator, cemimplimab-rwlc. This contribution highlights the importance of determining the immunological status of a patient who presents with metastatic disease following a complete tumor clearance.